2006
DOI: 10.21273/hortsci.41.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dynamic Climate on Energy Consumption and Production of Hibiscus rosa-sinensis L. in Greenhouses

Abstract: Production in a dynamic photosynthesis optimized climate (DC) was compared to production in a traditional and more stable climate (TC). Production of a tropical plant species (Hibiscus rosa-sinensis L.) in a DC resulted in between 18% and 63% reduction in energy use, mainly due to lower temperatures and increased use of thermal screens. In high light periods, the average day temperatures (ADT) were virtually the same in the different treatments, while in low light periods bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…During early spring, the greenhouse heated up mainly by irradiance leading to daytime temperatures up to 36°C, while at night ventilation with cool outdoor air allowed greenhouse air temperature to drop down to 24°C (Table 1). As a result, a positive DIF of 12°C could be obtained and saving energy is readily feasible according to Körner and Challa (2003), Lund et al (2006) and Körner and Van Straten (2008). In late autumn, however, low outdoor temperatures required supplementary greenhouse heating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During early spring, the greenhouse heated up mainly by irradiance leading to daytime temperatures up to 36°C, while at night ventilation with cool outdoor air allowed greenhouse air temperature to drop down to 24°C (Table 1). As a result, a positive DIF of 12°C could be obtained and saving energy is readily feasible according to Körner and Challa (2003), Lund et al (2006) and Körner and Van Straten (2008). In late autumn, however, low outdoor temperatures required supplementary greenhouse heating.…”
Section: Discussionmentioning
confidence: 99%
“…Growing ---Phalaenopsis therefore implies high heating expenses, especially in northern latitudes during winter. To reduce energy consumption, warm day/cool night temperature regimes have been proposed (Buwalda et al 2000, Lund et al 2006. However, taking into account that temperature is a main environmental factor influencing the metabolism and development of CAM plants (Lüttge 2004), further improvement of Phalaenopsis production in terms of greenhouse heating strategies in northern latitudes demands a better understanding of the planttemperature responses.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate climates, high-energy inputs can be required to maintain a desirable greenhouse temperature, making fuel for heating one of the largest floriculture production expenses (Bartok, 2001). Greenhouse growers can reduce energy consumption by managing the greenhouse environment with dynamic temperature control (DTC) strategies (Körner et al, 2007;Lund et al, 2006). In DTC, in contrast to static temperature control, heating set points are lowered during periods when the greenhouse energy loss factor is high (e.g., outside temperature and incoming solar radiation are low) and increased when the energy loss factor is low (Körner et al, 2004).…”
mentioning
confidence: 99%
“…This environmental control strategy integrates temperature and maintains a target MDT over a 1-to 7-d interval (Körner et al, 2004;Körner and Challa, 2003). Lund et al (2006) reported that a greenhouse in Denmark using DTC had 32% to 79% and 75% to 89% lower energy consumption for heating during winter and spring months, respectively, compared with a greenhouse using static temperature set points.…”
mentioning
confidence: 99%
“…The amount of energy saved in a dynamic climate control system depended strongly on the night temperature required by a given plant species. Lund et al (2006) recently demonstrated that it is possible to produce a heat-demanding plant (Hibiscus rosa-sinensis) in a system where the temperature is allowed to drop to a minimum set-point of 15°C.…”
mentioning
confidence: 99%